Multifocal Epithelial Hyperplasia of Oral Cavity Expressing HPV 16 Gene: A Rare Entity - M. P. V. Prabhat; Chintamaneni Raja Lakshmi; N. Sai Madhavi; Sujana Mulk Bhavana; Gummadapu Sarat; Kodali Ramamohan (Hindawi Limited, 2013)
Focal epithelial hyperplasia is a rare contagious disease caused by human papilloma virus. Usually HPV involves either cutaneous or mucosal surfaces, whereas concomitant mucocutaneous involvement is extremely rare. We report such a unique case of multifocal epithelial hyperplasia involving multiple sites of oral cavity along with skin lesions in a 65-year-old female. We also discuss the probable multifactorial etiology and variable clinical presentations of the lesions, including evidence of HPV 16 expression, as detected by polymerase chain reaction. The present report illustrates the need for careful examination and prompt diagnosis of the disease, as it might be associated with high risk genotypes such as HPV 16 and 18.